The ethics of autonomous neurosurgical robots (ANRs) - Townsend, Arturo Balaguer (Bioethics, 2025)
It may only be a handful of years before fully autonomous neurosurgical robots (ANRs) are pushed into widespread clinical adoption. Nevertheless, whether it is ethical to greenlight the development and adoption of ANRs is still up for debate. On the one hand, the widespread adoption of ANRs may lead to unprecedented therapeutic effects, increase sterility, improve pain profiles, increase precision, and reduce complications over the long term. On the other hand, ANRs may lead to human neurosurgical skill atrophy, increased legal uncertainty, increased burnout rates, and may produce no significant effect on pain profiles or complication rates, all of which may put patients at novel levels of risk. At this watershed, it is critical for stakeholders to preemptively deliberate about whether they would ultimately agree to these ethical trade-offs and decide to consciously support, thus help usher in the advent of autonomous neurosurgical technology.